Assessing trust with injected health information in Poland's healthcare system: Lay people versus healthcare workers. Issue 1 (2nd January 2023) - Lewandowski, Roman; Goncharuk, Anatoliy G.; Cirella, Giuseppe T.
Abstract : Health information can influence patient trust and is vital to the healthcare system of a country. This study comparatively assesses trust levels within Poland's healthcare system from two perspectives: non-healthcare workers (i.e. lay people) and healthcare workers. Four trust indicators, i.e. the payer, visiting or consulting with a physician, the medical profession, and hospitals are used to test trust volatility. The methodology combined a participant three-stage experiment by measuring level of trust, randomly separating participants into two groups – i.e. control and experimental – and testing whether observational changes were long-lasting. Results indicate that the level of trust of non-healthcare workers to the payer, a physician, and hospitals was susceptible to the information provided, while trust to the medical profession did not show sensitivity and almost did not change. Statistical analysis showed the non-healthcare workers trust level in all tested objects, apart from the medical profession, tended to return to their start values. Healthcare workers, on the other hand, had an overall higher level of trust in a physician, the medical profession, and hospitals. Overall, it can be concluded that the impact from the intervention in terms of hospitals was lower for the healthcare workers.